Classical and molecular cytogenetic characterization of Agonostomus monticola, a primitive species of Mugilidae (Mugiliformes) - Nirchio, Mauro; Oliveira, Claudio [UNESP]; Ferreira, Irani A. [UNESP]; Martins, Cesar [UNESP]; Rossi, Anna Rita; Sola, Luciana (Springer, 2009)
This study reports the first description of the karyotype of Agonostomus monticola, a species belonging to a genus which is considered to be the most primitive among living mugilid fish. Specimens from Panama and Venezuela were cytogenetically analysed by conventional chromosome banding (Ag and base-specific-fluorochrome staining, C-banding) and by fluorescent in situ hybridization (FISH). Agonostomus monticola showed a chromosome complement of 2n = 48, composed of 23 acrocentric and one subtelocentric chromosome pairs and a pericentromeric distribution of the C-positive heterochromatin in all chromosomes. Major ribosomal genes were found to be located on the short arms of the subtelocentric chromosome pair number 24 and minor ribosomal genes in a paracentromeric position of a single medium-sized chromosome pair. All these observed cytogenetic features are similar to those previously described in four representatives of two genera, Liza and Chelon, which are considered to be among the most advanced in the family. Thus, this karyotypic form might represent the plesiomorphic condition for the mullets. This hypothesis regarding the plesiomorphic condition, if confirmed, would shed new light on the previously inferred cytotaxonomic relationships for the studied species of Mugilidae, because the karyotype with 48 acrocentric chromosomes, which has been so far regarded as primitive for the family, would have to be considered as derived.
Keywords: Constitutive heterochromatin; FISH; Karyotype; 18S and 5S rDNA; NORs